Hydrogenated black TiO sub(2) nanowires decorated with Ag nanoparticles as sensitive and reusable surface-enhanced Raman scattering substrates - Shan, Yufeng; Yang, Yong; Cao, Yanqin; Yin, Hao; Long, Nguyen Viet; Huang, Zhengren (RSC advances, 2015)
Recently, surface-enhanced Raman scattering (SERS) has been the subject of great interest because of its ultrasensitive, rapid and nondestructive analysis, detection, and imaging. Highly sensitive, stable and recyclable substrates are of great importance in fulfilling the practical potential of the technique in various fields, such as trace analysis, diagnosis and criminal investigation. In this work, we introduce wafer-scale Ag-modified hydrogenated black TiO sub(2) nanowires as active SERS substrate by hydrogenation. The Ag/H-TiO sub(2) NWs substrates deliver a relative enhancement factor of up to similar to 10 super(2) compared with the substrate before hydrogenation and a detection limitation improved by at least three orders of magnitude compared with R6G detection. Moreover, hydrogenated TiO sub(2)/Ag also exhibits outstanding stability, and is recyclable by self-cleaning under UV irradiation. The excellent SERS performance is ascribed to the abundant surface electronic states induced by the hydrogenated amorphous layers and trivalent titanium, and more photogenerated charge carriers may contribute to the chemical and electromagnetic enhancement. The relative standard deviation (RSD) value for Raman signals less than 0.15 confirms the reproducibility of the hydrogenated composite SERS substrate. Therefore, the hybrid SERS substrates have great advantages in self-cleaning, reproducibility and stability, making them promising candidates for sensitive and recyclable SERS detection.